Strategi Komisi Pemilihan Umum (KPU) Dalam Meningkatkan Partisipasi Masyarakat Pada Pemilihan Umum Kepala Daerah - Tulkah Husen; Tri Sosilowati (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Public political participation in the implementation of regional elections is a very important aspect so that the General Election Commission uses a special strategy to increase public participation in the implementation of regional elections. This research is a normative research with the approach used is a conceptual approach and statute approach. The results of this study are, KPU strategy in each region in increasing public political participation in the election in the coming year can be seen from three stages, namely the formulation stage shows there is clarity of socialization planning from KPU. Second, the action selection stage, the KPU carries out socialization to eight segments of voters with the socialization method in the form of face-to-face and the use of mass media with the implementation pattern adjusted to the characteristics of the intended area. The third stage of resource allocation is by conducting technical guidance to the ad hoc committee. The obstacles experienced by the KPU are the lack of budget, community apathy, and the limited number of KPU personnel.